Analysis of the Influence of Discount Promotions on Students' Purchase Decisions on the Shopee E-Commerce Platform - Jessica Fernanda Audrelya; Moh Hafis Xafier; Nurul Maisyaroh; Muhammad Alkirom Wildan (Badan Penerbit STIEPARI Press, 2025)
This study aims to understand the impact of discount promotions on consumer purchasing decisions on the Shopee platform. In today's digital era, e-commerce has brought major changes in people's shopping patterns, where discounts are one of the most attention-grabbing strategies. Through a quantitative approach, data was collected from 100 students of Trunojoyo University Madura who are active users of Shopee. The results showed that discounts have a real influence on purchasing decisions. Discounts are not only able to attract consumers' attention, but also encourage them to make purchases immediately and build loyalty to the platform. This finding reinforces that discount promotion is still one of the effective marketing strategies in the face of fierce competition in the e-commerce industry.